Collagen Gene Variants and Anterior Cruciate Ligament Rupture in the Korean Population - Ki-Hoon Seong; Kwang-Jun Kim; Hee-Jung Park; Byung-Hoon Lee; Eunwook Chang; Dong-Ho Park (운동과학)
PURPOSE Anterior cruciate ligament rupture (ACLR) is a common knee ligament injury that occurs in sports. The precise etiology of ACLR remains unknown. Previous studies in various ethnic groups have confirmed an association between genetic variants and ACLR; however, no such research has been conducted in Koreans. This study aimed to investigate whether certain single nucleotide polymorphisms (SNPs), namely COL3A1 rs1800255, COL5A1 rs12722, COL12A1 rs970547, and COL5A1 rs13946, are associated with ACLR in the Korean population. METHODS This study involved 60 ACLR patients (ACL group, average age 29.9±10.9 years) and 328 control subjects (CON group, average age 23.8±4.1 years). All the participants were genotyped for COL3A1 rs1800255, COL5A1 rs12722, COL12A1 rs970547, and COL5A1 rs13946. RESULTS No significant genotypic differences were found for COL3A1 rs1800255 (p=.565), COL5A1 rs12722 (p=.779), COL12A1 rs970547 (p=.193), or COL5A1 rs13946 (p=.356). Furthermore, no significant differences were observed between the homozygous and dominant models for each SNP or between the haplotypes of COL5A1 rs12722 and rs13946 (p=.118). However, a significant association with ACLR was observed for the genotype combinations COL3A1 rs1800255 and COL5A1 rs12722 (p=.02). CONCLUSIONS The results of this study indicate that specific genotypes (SNPs) COL3A1 rs1800255 and COL5A1 rs12722 may influence the occurrence of ACLR. Considering the results and limitations of this study, future research should focus on increasing the sample size, particularly by including both male and female patients of diverse ages, to further validate these findings.